The phase transitions in directed acyclic graphs - Kassaye, Masreshaw Temere (Stellenbosch : Stellenbosch University, 2025)
Kassaye, M. T. 2025. The Phase Transitions in Directed Acyclic Graphs. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/e00e14f4-4a03-4ed8-aaa2-c6270a476561